Hypotheses and Conclusions in Research on Educational Quality. An Analysis of Coherence in Graduate Theses - Venegas-Mejía , Valia; Esquivel-Grados, José; Herrera Álvarez, Angela María; Vásquez Tomás, Melba Rita; Baldeón De La Cruz, Maruja Dionisia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The purpose of the study was to analyze the coherence of the presentation of hypotheses and conclusions in postgraduate thesis on educational quality, which was carried out with a descriptive design. The population consisted of postgraduate theses on educational quality from four Universities of Lima, supported from 2020 to 2022, and the sample was adequate and representative. After the documentary review and analysis, the statistical analysis allowed us to find as a result a weak linear positive correlation of such variables with a significance much lower than 0.01, which means that there is no optimal logical articulation between elements of the these.